The Effectiveness of Seaweeds as Biofilter for Reducing Wastewater Nutrient and Preventing Water Pollution from Hybrid Grouper Culture - Ratih Ida Adharini; Murwantoko Murwantoko; Namastra Probosunu; Riza Yuliratno Setiawan; Tony Budi Satriyo (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight ResearchWastewater in hybrid grouper culture should be maintain before resirculate and dispose to aquatic environment to avoid eutrophication.Seaweed that is used for biofilter must be observed for its suitability, performance and effectivity.Ulva sp. has the best effectiveness to reduce nutrient in wastewater of hybrid grouper aquaculture by absorbing then stored into thallus.Ulva sp. is proven has the best SGR and adaptability in wastewater of hybrid grouper culture.AbstractWastewater generated from hybrid grouper culture needs to be managed to improve water quality before being recirculated, or discharged in the aquatic environment. Seaweed biofilter has been proposed in wastewater treatment technology for marine fish farming. This study aimed at comparing which of these species i.e. Ulva sp., Sargassum sp., Gelidium sp., and Dictyota sp.  work best to absorb nutrient wastewater hybrid grouper culture. This research utilized these seaweed as treatments and controls with three replications using Completely Randomized Design. A statistical analysis was conducted to investigate the significant differences in the nutrient absorptions among various seaweed species by using ANOVA and least significant difference. Non-parametric tests namely Kruskal-Walis, Mann-Whitney, and t-test were used with confidence interval of 95%. The results revealed that Ulva sp. has the best ability to reduce the Nitrogen 80%, while Dictyota able to reduce  Phosphor 88% by Dictyota sp. generated from wastewater of hybrid grouper culture. While the highest absorbtion of Total Kjeldahl Nitrogen (104%) and phosphate (182%) that stored in thallus were performed by Ulva sp. Ulva sp. had the best performance and highest growth rate (1.9% d-1) as biofilter in hybrid grouper cultivation than other species.